Solid particle erosion and scratch behavior of novel scrap carbon fiber/glass fabric/polyamide 6.6 hybrid composites - Kocoglu, Hurol; Korkusuz, Orkan Baran; Ozzaim, Pelin; Kodal, Mehmet; Altan, M. Cengiz; Sinmazcelik, Tamer; Ozcelik, Babur (Wiley, 2023)
This study investigated the tribological performance of hybrid composites composed of scrap carbon fiber (CF), glass fabric (GF), and polyamide 6.6 (PA6.6) through an innovative approach for reusing scrap CFs in high-value composite structures. The experimental setup included CF/GF/PA6.6 hybrid composite laminates with varying CF contents and surface-modified GFs, as well as PA6.6 sheets and GF/PA6.6 composite laminates. Solid particle erosion and scratch tests were conducted to assess the influence of scrap CF hybridization and GF surface modification on the tribological properties of the composites. The results demonstrated that neat PA6.6 sheets exhibited the lowest erosion rate, while the incorporation of CF and GF reinforcements had a detrimental effect on erosion resistance. The highest erosion rate was observed within the impact angle range of 15 degrees -30 degrees for pure PA6.6 sheets, whereas for composite laminates, it occurred within the range of 30 degrees-45 degrees. In contrast, CFs positively affected scratch hardness despite their negative impact on erosion resistance. Additionally, the silane treatment of GFs, which enhanced interfacial strength, improved the erosion resistance and scratch hardness of GF/PA6.6 composite laminates without CF. Profilometer-based topographic analysis revealed a correlation between the average surface roughness of the eroded surfaces and the weight loss resulting from solid particle erosion.
Keywords: polymer matrix composites; scrap carbon fiber; silane treatment; surface analysis; wear